Pengaruh Penerapan Teknologi Informasi Dan Pemeriksaan Pajak Terhadap Kepatuhan Wajib Pajak Parkir. - Muhammad Ihsan Apriyadi Dwi Putra (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2020)
This study aims to determine the effect of the application of information technology and tax audits on parking taxpayer compliance at the Regional Financial Management Agency of West Bandung Regency. The research approach used in this research is descriptive and verification analysis. By using primary data. The sample used is using saturated samples. The statistical analysis used in this study is the classic assumption test, normality assumption test, heteroscedasticity assumption test, simple linear regression, and hypothesis test correlation test. The number of research population is 67 people, the research sample used is 67 people with the source of data obtained through the results of filling out the questionnaire. Based on the results of research conducted can be seen that partially the application of information technology and tax audits affect the compliance of parking taxpayers. The magnitude of the influence of the application of information technology is 27.0% and tax collection has an effect of 35.7%. While the rest, namely the application of information technology 73.0 and tax audits of 64.3 are other factors beyond the two independent variables not examined.